(untitled) (Analele Universitatii din Bucuresti – Seria Istorie, 2024)
The article takes into consideration the idea and the imperial action through the geostrategic approach, that is the approach focused on the balance of power between different countries considered in relation to space. From this point of view, the empire represents a form of domination exercised by hegemonic power over other countries, especially by military means. We then see several examples of imperial policy related to geography during the XIXth century and the XXth century. We finish with some considerations concerning the contemporary situation, that is to say the confrontation between the United States of America and Russia.